Cathepsin K-deficiency impairs mouse cardiac function after myocardial infarction. (February 2019) - Fang, Wenqian; He, Aina; Xiang, Mei-Xiang; Lin, Yan; Wang, Yajun; Li, Jie; Yang, Chongzhe; Zhang, Xian; Liu, Cong-Lin; Sukhova, Galina K.; Barascuk, Natasha; Larsen, Lise; et al.
Abstract: Background: Extracellular matrix metabolism and cardiac cell death participate centrally in myocardial infarction (MI). This study tested the roles of collagenolytic cathepsin K (CatK) in post-MI left ventricular remodeling. Methods and results: Patients with acute MI had higher plasma CatK levels (20.49 ± 7.07 pmol/L, n = 26) than those in subjects with stable angina pectoris (8.34 ± 1.66 pmol/L, n = 28, P = .01) or those without coronary heart disease (6.63 ± 0.84 pmol/L, n = 93, P = .01). CatK protein expression increases in mouse hearts at 7 and 28 days post-MI. Immunofluorescent staining localized CatK expression in cardiomyocytes, endothelial cells, fibroblasts, macrophages, and CD4 + T cells in infarcted mouse hearts at 7 days post-MI. To probe the direct participation of CatK in MI, we produced experimental MI in CatK-deficient mice ( Ctsk −/− ) and their wild-type ( Ctsk +/+ ) littermates. CatK-deficiency yielded worsened cardiac function at 7 and 28 days post-MI, compared to Ctsk +/+ littermates (fractional shortening percentage: 5.01 ± 0.68 vs. 8.62 ± 1.04, P < .01, 7 days post-MI; 4.32 ± 0.52 vs. 7.60 ± 0.82, P < .01, 28 days post-MI). At 7 days post-MI, hearts from Ctsk −/− mice contained less CatK-specific type-I collagen fragments (10.37 ± 1.91 vs. 4.60 ± 0.49 ng/mg tissue extract, P = .003) and more fibrosis (1.67 ± 0.93 vs. 0.69 ± 0.20 type-III collagen positive area percentage, P = .01; 14.25 ± 4.12 vs. 6.59 ± 0.79 α-smooth muscle actin-positive area percentage, P = .016; and 0.82 ± 0.06 vs. 0.31 ± 0.08 CD90-positive area percentage, P = .008) than those of Ctsk +/+ mice. Immunostaining demonstrated that CatK-deficiency yielded elevated cardiac cell death but reduced cardiac cell proliferation. In vitro studies supported a role of CatK in cardiomyocyte survival. Conclusion: Plasma CatK levels are increased in MI patients. Heart CatK expression is also elevated post-MI, but CatK-deficiency impairs post-MI cardiac function in mice by increasing myocardial fibrosis and cardiomyocyte death. Highlights: Plasma levels of CatK increase in patients with CHD particularly during AMI, compared to controls. CatK is expressed in cardiomyocytes, endothelial cell, fibroblast, macrophage, and CD4 + T-cell from post-MI mouse heart. In post-MI heart, CatK-deficiency increases fibrosis and cell death, and impairs cell proliferation and cardiac function. CatK inhibition or deficiency increases cardiomyocyte death, but suppresses CD4 + T-cell and macrophage death.